2015
DOI: 10.1111/edt.12222
|View full text |Cite
|
Sign up to set email alerts
|

Enamel fracture in the primary dentition has no impact on children's quality of life: implications for clinicians and researchers

Abstract: Aim:To quantify the impact of traumatic dental injuries (TDI) on Oral Health Related Quality of Life (OHRQoL) of preschool children, when enamel fractures were either included or excluded within the category of TDI. Material and Methods: An oral health survey was undertaken of preschool children, age 1-5 years attending public nurseries in Canoas, Brazil. Children were examined for TDI, dental caries and malocclusion. Parents were interviewed on their perception of their child's OHRQoL (Early Childhood Oral He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 30 publications
2
49
1
2
Order By: Relevance
“…However, traumatic dental injuries with enamel fracture adjusted for the same variables had no impact on the OHRQoL. 13,23 Silva-Oliveira et al 4 found that 34.4% of 12-year-olds with a negative impact on the quality of life suffered dental trauma to at least 1 or more teeth. 22 The children in the present study with enamel-dentin fracture had higher prevalence of impact on oral symptoms measured with the CPQ 8-10, when compared with those who had no traumatic dental injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, traumatic dental injuries with enamel fracture adjusted for the same variables had no impact on the OHRQoL. 13,23 Silva-Oliveira et al 4 found that 34.4% of 12-year-olds with a negative impact on the quality of life suffered dental trauma to at least 1 or more teeth. 22 The children in the present study with enamel-dentin fracture had higher prevalence of impact on oral symptoms measured with the CPQ 8-10, when compared with those who had no traumatic dental injuries.…”
Section: Discussionmentioning
confidence: 99%
“…4,12 Some articles present an association between the negative impact on oral health-related quality of life (OHRQoL) and dental trauma. This becomes clearer when studies such as that of Feldens et al 13 are evaluated, where the authors made a distinction between the types of fracture in primary teeth and they found a relationship with the OHRQoL and enamel plus dentin fracture or more severe injury but no association with enamel fracture. 1,2,4 However, to study the relationship between these variables, it is necessary to create a separation according to the signs of dental trauma, as joining all the fractures in only 1 group may present a confusing association, without knowing which fracture was actually related to the OHRQoL.…”
mentioning
confidence: 99%
“…It has been shown that traumatic injuries to primary teeth represent one of the most common aetiologic factors of eruption disturbances of permanent teeth, including premature eruption, delayed eruption or impactions 15,19,20 . There are reports, as well that some dental injuries have no significant impact on young children's quality of life 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic dental injury (TDI) is considered a public health problem that requires long‐term expenses and care. The prevalence among preschool children ranges from 13.4% to 62.1% and this condition can affect quality of life . Thus, it is important to evaluate the association between TDI and OHRQoL in this population.…”
Section: Introductionmentioning
confidence: 99%